Mitochondrial Respiration in KRAS and BRAF Mutated Colorectal Tumors and Polyps - Egle Rebane-Klemm (Cancers, 2020)
This study aimed to characterize the ATP-synthesis by oxidative phosphorylation in colorectal cancer (CRC) and premalignant colon polyps in relation to molecular biomarkers KRAS and BRAF. This prospective study included 48 patients. Resected colorectal polyps and postoperative CRC tissue with adjacent normal tissue (control) were collected. Patients with polyps and CRC were divided into three molecular groups: KRAS mutated, BRAF mutated and KRAS/BRAF wild-type. Mitochondrial respiration in permeabilized tissue samples was observed using high resolution respirometry. ADP-activated respiration rate (Vmax) and an apparent affinity of mitochondria to ADP, which is related to mitochondrial outer membrane (MOM) permeability, were determined. Clear differences were present between molecular groups. KRAS mutated CRC group had lower Vmax values compared to wild-type; however, the Vmax value was higher than in the control group, while MOM permeability did not change. This suggests that KRAS mutation status might be involved in acquiring oxidative phenotype. KRAS mutated polyps had higher Vmax values and elevated MOM permeability as compared to the control. BRAF mutated CRC and polyps had reduced respiration and altered MOM permeability, indicating a glycolytic phenotype. To conclude, prognostic biomarkers KRAS and BRAF are likely related to the metabolic phenotype in CRC and polyps. Assessment of the tumor mitochondrial ATP synthesis could be a potential component of patient risk stratification.